2020
DOI: 10.21203/rs.3.rs-42179/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessing Current And Preferred Sources Of Information On Adolescents’ Sexual And Reproductive Health In Southeast Nigeria: Improving Adolescent Health Programming

Abstract: Background: Many adolescents lack appropriate information about their sexual and reproductive health (SRH). Although there are numerous information on SRH, they vary in content and quality, and these have implications for the accuracy and appropriateness of SRH information adolescents can access. This study examined the sources of SRH information for adolescents, the value adolescents place on these sources and their significance for adolescent health programming.Method: This was a mixed methods, community-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The quality of health promotion interventions through social media is very good (26). In contrast, in Agu et al (20) research, the accuracy of the information sources must be improved.…”
Section: Coverage and Qualitymentioning
confidence: 97%
See 3 more Smart Citations
“…The quality of health promotion interventions through social media is very good (26). In contrast, in Agu et al (20) research, the accuracy of the information sources must be improved.…”
Section: Coverage and Qualitymentioning
confidence: 97%
“…Social media has succeeded in meeting these needs and has exceeded the expectations of millennial teenagers (22). A review of 21studies showed, 90.4% of the studies showed an increase in knowledge, attitudes, or behavior toward providing reproductive health education to adolescents, while 9.6 considered that the internet still presented a contradictory perspective and provided a cultural shift (17,20). The results showed that 85.7% of adolescents used the social media sites Facebook and Instagram, of which 71.4% and 10.7% had a good and sufficient level of knowledge, respectively (23).…”
Section: Effectiveness Of Interventionsmentioning
confidence: 99%
See 2 more Smart Citations